Learning Morse Code Alters Microstructural Properties in the Inferior Longitudinal Fasciculus: A DTI Study - Schlaffke, Lara; Leemans, Alexander; Schweizer, Lauren M.; Ocklenburg, Sebastian; Schmidt-Wilcke, Tobias (Frontiers in Human Neuroscience, 2017)
Learning relies on neuroplasticity, which has mainly been studied in gray matter. However, there is mounting evidence indicating a critical role of white matter changes involved in learning processes. One of the most important learning processes in human development is language acquisition. However, due to the length of this learning process, it has been notoriously difficult to investigate the underlying neuroplastic changes. Here, we report a novel learning paradigm to assess the role of white matter plasticity for language acquisition. By using acoustically presenting Morse Code (MC) using an in house developed audio book as a model for language-type learning, we generated a well-controlled learning environment that allows for the detection of subtle white matter changes related to language type learning in a much shorter timeframe than usual language acquisition. In total 12 letters of the MC alphabet were learned within six learning session, which allowed study participants to perform a word recognition MC decoding task In this study, we found that learning MC was associated with significant microstructural changes in the left inferior longitudinal fasciculus (ILF),. The fractional anisotropy of this an associative fiber bundle connecting the occipital and posterior temporal cortex with the temporal pole as well as the hippocampus and amygdala was increased. Furthermore, white matter plasticity was associated with task performance of MC decoding, indicating that the structural changes were related to learning efficiency. In conclusion, our findings demonstrate an important role of white matter neuroplasticity for acquiring a new language skill.